Stem/progenitor cell-based therapy for Duchenne muscular dystrophy - Tominari, Tsukasa; Sathyaprakash, Chaitra; Aoki, Yoshitsugu (Frontiers in Cell and Developmental Biology, 2025)
Duchenne muscular dystrophy is a genetic disease where loss of sarcolemma-associated protein, dystrophin, leads to progressive muscle wasting, and eventual loss of life from complications linked to cardiac deficits. Currently, numerous molecular therapies to restore dystrophin have entered clinical trials. However, the therapeutic benefits of these strategies in promoting tissue regeneration and reducing fibrosis remain limited. Stem/progenitor cell-based therapy in DMD patients is a promising strategy to promote muscle regeneration, though the conditions of transplantation and pre-treatments of numerous cell types are still being optimized. Several cell types with different properties and origins, such as myogenic stem/progenitor cells, mesenchymal stem cells (MSCs), and induced pluripotent stem cells (iPSCs), have been studied for treating DMD. Myogenic stem/progenitor cells derived from healthy donors are expected to restore the number of myofibers as well as dystrophin expression in DMD muscles. MSCs derived from various tissues, including umbilical cord, have immunosuppressive properties and are expected to ameliorate DMD phenotypes in combination with other gene therapies. In this review, we will summarize the challenges that must be overcome to allow for successful DMD muscle tissue regeneration and review the latest findings in stem/progenitor cell-based DMD therapy. We will focus on the pre-conditioning of cells for replacement therapies and treatment of the disease niche to improve muscle fiber integration.